2017
DOI: 10.3892/ijo.2017.4033
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of long non-coding RNA and mRNA expression associated with acquired temozolomide resistance in glioblastoma cells

Abstract: Temozolomide (TMZ) is an alkylating chemotherapeutic agent widely used in anti-glioma treatment. However, acquired TMZ resistance represents a major clinical challenge that leads to tumor relapse or progress. This study investigated the genomic profiles including long non-coding RNA (lncRNA) and mRNA expression associated with acquired TMZ resistance in glioblastoma (GBM) cells in vitro. The TMZ-resistant (TR) of GBM sub-cell lines were established through repetitive exposure to increasing TMZ concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Thus, genomic characterization of lncRNA alterations may provide an alternative therapeutic strategy for TMZ-resistant GB. Previously, our microarray analysis showed 2,692 lncRNAs and 2,933 mRNAs exhibiting a change of more than 2.0-fold in TMZ-resistant U87 (U87TR) cells 20 . Of note, lncRNA AC003092.1 and its nearby gene, itssue factor pathway inhibitor-2 (TFPI-2), showed a remarkable downregulation in U87TR cells when compared with its parental U87 cells (43.99 folds and 607.05 folds, respectively) 20 .…”
Section: Introductionmentioning
confidence: 93%
“…Thus, genomic characterization of lncRNA alterations may provide an alternative therapeutic strategy for TMZ-resistant GB. Previously, our microarray analysis showed 2,692 lncRNAs and 2,933 mRNAs exhibiting a change of more than 2.0-fold in TMZ-resistant U87 (U87TR) cells 20 . Of note, lncRNA AC003092.1 and its nearby gene, itssue factor pathway inhibitor-2 (TFPI-2), showed a remarkable downregulation in U87TR cells when compared with its parental U87 cells (43.99 folds and 607.05 folds, respectively) 20 .…”
Section: Introductionmentioning
confidence: 93%
“…Increasing evidence has indicated the existence of a key population of glioblastoma cells with stem cell properties, referred to as glioma stem-like cells (GSCs; Nguyen et al, 2012 ), that are thought responsible for tumor genesis, the propagation of disease, the resistance to current chemotherapy and cancer recurrence (Filatova et al, 2013 ). Various research groups have proposed diverse hypotheses accounting for treatment failure in some patients with malignant glioma, including O 6 -methylguaninine-DNA-methytransferase gene methylation, isocitrate dehydrogenase gene mutations, aberrant ATP-binding cassette (ABC) transporter expression, p53 mutations and deletions, DNA repair deregulation, micro (mi)RNAs and long non-coding RNAs (Zeng et al, 2017 ). In addition to such concerns, the impact of the tumor microenvironment in various stem cell niches have been described in recent studies (Faissner and Reinhard, 2015 ), with several breakthroughs as a result of successfully growing stem cells on naturally-derived and synthesized substrates (Lee et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, one of the most hot targets in glioma TMZ resistance is the discovery of lncRNAs and their key roles. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Constitutively activate NF-κB is a major transcription factor linked with glioma, and it may be responsible for multiple cellular functions including apoptosis inhibition and promotion of survival, invasion and immune response. 32 Activation of NF-κB signaling is also accompanied by the acquisition of TMZ resistance in glioma. 30 Our results showed that H19 knockdown inhibited NF-κB signaling as revealed by decreased NF-κB reporter activity and target expression, whereas H19 overexpression resulted in the activated NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%